2004
DOI: 10.1080/13651500310003868
|View full text |Cite
|
Sign up to set email alerts
|

Major depression versus dysthymia: Comorbid psychiatric disorders, psychotropic medication patterns, and psychotherapy sessions

Abstract: The objective of this study was to examine, among those with major depression versus dysthymia, relationships with comorbid psychopathol-ogy, patterns of psychotropic medication prescription, and number of psychotherapy sessions utilized. Using a retrospective approach, a single investigator reviewed the medical records of individuals diagnosed with major depression or dysthymia (those with both disorders were excluded from analysis) in an adult, university-based, outpatient psychiatry clinic. Records were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Dysthymia often coexists with medical conditions (Sansone, Gaither, & Rytwinski, ). In this study, compared to MDD without dysthymia, MDD patients with dysthymia was had more frequent atypical depressive features (increased appetite, sleep, and weight gain) that could contribute to increased risk of metabolic syndrome (Murray, Weiner, Prabhakar, & Fiedorowicz, ).…”
Section: Discussionsupporting
confidence: 85%
“…Dysthymia often coexists with medical conditions (Sansone, Gaither, & Rytwinski, ). In this study, compared to MDD without dysthymia, MDD patients with dysthymia was had more frequent atypical depressive features (increased appetite, sleep, and weight gain) that could contribute to increased risk of metabolic syndrome (Murray, Weiner, Prabhakar, & Fiedorowicz, ).…”
Section: Discussionsupporting
confidence: 85%
“…Many researchers have reported the spectrum theory of depressive disorders [8][9][10][11]. Sansone et al [12] reported that university students with dysthymia were significantly more likely to be diagnosed with a personality disorder than those with major depression were. In contrast, another study found essentially temperamental differences between adolescents with major depression and those with dysthymia [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the Ministry of Health, Labour and Welfare advocates training of the "gatekeeper" as a comprehensive measure to prevent suicide. Several articles have reported the effectiveness of suicide prevention gatekeepertraining for university staff [3,12]. If such measures are more widely implemented, it may lead to the prevention of more suicides.…”
Section: Discussionmentioning
confidence: 99%